Dragon to the rescue - Kann, Victoria (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
When Pinkalicious and her friends try to roast marshmallows at a backyard camping party, it is too windy to keep the campfire lit, but luckily, Gertie the dragon steps in to help out.
jla09/19.
Keywords: Pinkalicious -- (Fictitious character) -- Juvenile fiction; Campfires -- Juvenile fiction; Dragons -- Juvenile fiction